Applications of network coding to improve TCP performance over wireless mesh networks: a survey. Issue 13 (7th June 2012) - Arianpoo, Nasim; Jokar, Paria; Leung, Victor C.M.
ABSTRACT There is growing interest in the use of wireless mesh network (WMN) as a last‐mile option for Internet access. Despite the many benefits of WMNs, the performance of Internet access may not be ideal. One of the main issues is the interaction of transmission control protocol (TCP) with the underlying network. The poor performance of TCP over multi‐hop networks is well‐documented, and extensive research exists, which addresses TCPs foible and enhance TCP performance for multi‐hop environments. This paper provides a thorough survey of TCP performance issues over WMNs and the available solutions to address these issues. Among the existing methods, we focused on network coding (NC) and the ways that TCP interacts with network coded systems. NC is a technique that encodes the received packets in each node before forwarding them towards the destination. The use of NC in the transport layer to address performance issues raised by wireless access is a recent research topic. This paper presents a detailed study of TCP interaction with NC. Some open research areas in this field are suggested. Copyright © 2012 John Wiley & Sons, Ltd.